Achieving a quantum smart workforce. (16th June 2021) - Aiello, Clarice D; Awschalom, D D; Bernien, Hannes; Brower, Tina; Brown, Kenneth R; Brun, Todd A; Caram, Justin R; Chitambar, Eric; Di Felice, Rosa; Edmonds, Karina Montilla; Fox, Michael F J; Haas, Stephan; et al.
Abstract: Interest in building dedicated quantum information science and engineering (QISE) education programs has greatly expanded in recent years. These programs are inherently convergent, complex, often resource intensive and likely require collaboration with a broad variety of stakeholders. In order to address this combination of challenges, we have captured ideas from many members in the community. This manuscript not only addresses policy makers and funding agencies (both public and private and from the regional to the international level) but also contains needs identified by industry leaders and discusses the difficulties inherent in creating an inclusive QISE curriculum. We report on the status of eighteen post-secondary education programs in QISE and provide guidance for building new programs. Lastly, we encourage the development of a comprehensive strategic plan for quantum education and workforce development as a means to make the most of the ongoing substantial investments being made in QISE.